Profile of Students' Creative Thinking in Solving Mathematical Problems in terms of Gender - Kharisma Isrozia Kusumawardhany; Mega Teguh Budiarto; Raden Sulaiman (Department of Mathematics Education University of Muhammadiyah Malang, 2022)
Creative thinking is a person's mental activity related to sensitivity to problems, considering new information and unusual ideas with an open mind, generating alternative answers, and fulfilling the components of fluency, flexibility, and novelty. So far, gender differences have been referred to as one of the factors that affect students' creative thinking skills in solving problems. The purpose of this study was to describe students' creative thinking in solving math problems in terms of gender. This research is a qualitative descriptive study. The subjects of this study were 2 junior high school students in grade VII, where one student was male and one female student. The instrument in this study was a test of mathematical ability, problem-solving assignments, and interview guidelines. This study began by determining the research subject using a mathematical ability test then the researcher gave problem-solving tasks and interviews to each subject. The results obtained are a description of the creative thinking of male students and a description of the creative thinking of female students in solving math problems.